2017
DOI: 10.5603/gp.a2017.0049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of low molecular weight heparin on obstetric outcomes among unexplained recurrent miscarriages complicated with methylenetetrahydrofolate reductase gene polymorphism

Abstract: Objectives:The association between methylenetetrahydrofolate reductase gene polymorphisms and unexplained recurrent miscarriage is elusive. The recommendations for improving pregnancy outcomes in these patients keep changing based on the available evidence. The aim of this study is to analyze the impact of low molecular weight heparin on obstetric outcomes of recurrent miscarriage patients complicated with methylenetetrahydrofolate reductase gene polymorphism. Material and methods:We reviewed medical records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…LMWH group had higher live birth rate (69.8% vs. 48.5%, p = 0.015) and lower congenital anomalies rate (3.3% vs. 17.6%, p = 0.022). Treatment group delivered two weeks later (34.88 vs. 32.75) comparing with supplementation only group but this result did not reach statistical significance (p = 0.060) [30].…”
Section: Potential Therapiesmentioning
confidence: 80%
“…LMWH group had higher live birth rate (69.8% vs. 48.5%, p = 0.015) and lower congenital anomalies rate (3.3% vs. 17.6%, p = 0.022). Treatment group delivered two weeks later (34.88 vs. 32.75) comparing with supplementation only group but this result did not reach statistical significance (p = 0.060) [30].…”
Section: Potential Therapiesmentioning
confidence: 80%
“…Studies revealed that placental thrombosis, vascular endothelial growth factor dysfunction, and maternal-fetal immunology play a role in women with URPL [3,4]. Proinflammatory changes such as increased Th1 to Th2 cytokine ratio and complement activation has been repeatedly demonstrated in these women [3,4,5]. There is also increasing knowledge of the association between methylenetetrahydrofolate reductase gene polymorphisms and URPL [5].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory changes such as increased Th1 to Th2 cytokine ratio and complement activation has been repeatedly demonstrated in these women [3,4,5]. There is also increasing knowledge of the association between methylenetetrahydrofolate reductase gene polymorphisms and URPL [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations